Analysis Of Policy Formulation And Implementation Of Stunting Reduction In Penajam Paser Utara District In 2021 - Tri Utami; Kosasih Kosasih; Rukhiyat Sayidin (Journal on Education, 2023)
One of the most crucial nutritional problems is stunting or short toddlers, especially in poor and developing countries. Of the 100 districts with special stunting locations set by the central government in 2018, one of them is Penajam Pasar Utara District. The local government has issued a policy through Regent Regulation No. 34 of 2019 concerning the Acceleration of Reducing and Prevention of Stunting which is a guideline for the implementation of integrated stunting reduction and prevention programs. This research aims to analyze the formulation and implementation of stunting reduction policies. The approach used in this study is a qualitative approach. The research data were obtained from interviews and observations. The results of this study indicate that the formula for accelerating the reduction of stunting includes integration of cross-sectoral programs to accelerate, reduce and prevent stunting ; implementation of policies to accelerate reduction and prevention of stunting implementation across sectors in a convergent manner and with comprehensive behavior change